A Theoretical Evaluation of the Socio Economic Influence on the Employees of Bangladesh - Chowdhury , Md. Mosaddeak Khan (Global Disclosure of Economics and Business, 2016)
Human behavior in the sphere of life in general and in the area of job, in particular, depends on both internal and external factors. There are many well-accepted academic theories in regard to internal factors that affect job environment of the employees which eventually lead to their satisfaction or dissatisfaction. The external factors have not got such attention because these are country- specific and culture-specific phenomenon. Each country has its uniqueness which forms unique characteristic within her habitants. These country characteristics depend on various factors, and the fundamentals are those that are apparently beyond the immediate control of their people. History, topography, weather, socio-economic status of the people are few of the prominent factors that affect the job environment of most of the people of any particular country. In this paper, a theoretical evaluation of the effects of such prominent factors has been outlined keeping a farther scope to verify the postulates with real-time data.JEL Classification Code: A 14; J 08; Z 13